THE EFFECT OF NATURAL APPROACH TOWARDS STUDENTS’ SPEAKING MASTERY X GRADE - SMA NEGERI 3 – PADANGSIDIMPUAN - Zainuddin M.Pd (JURNAL LINER (Language Intelligence and Educational Research), 2020)
ABSTRACT : The research focused on the effect of natural approach towards students’ speaking mastery X grade - SMA Negeri 3 - Padangsidimpuan. There are students’ problems in speaking mastery like: 1) students are low in speaking mastery, 2) students feel shy to speak English, especially in front of class, 3) students often mispronounce words and they usually speak English in incorrect structure and grammar. Moreover, the teacher does not use suitable approach in teaching process. The purpose of this research is to know whether there is or there is not the effect of natural approach on students’ speaking mastery X grade - SMA Negeri 3 - Padangsidimpuan.The used method of the research is experimental research. Where as the population of the research is 6 classes at the X grade of SMA Negeri 3 Padangsidimpuan, then the total population is 230 students. Consequently, two classes were chosen randomly as the sample. They were X MIA-1 as experiment class that consists of 40 students and X MIA-2 as control class that consists of 40 students. The data is taken from pre-test and post-test. To analyze the data, the researcher uses t-test formula.After analyzing the data, the researcher finds that mean score of experimental class after using Natural Approach is higher than control class. Mean score of experimental class and control class in pre test is (59.34 < 63.7), mean score experimental class and control class in post test was (79.25 > 72.48). Besides, the score of tcount was bigger than ttable (3.18 > 2.00). It means that the hypothesis alternative (Ha) is accepted and H0 is rejected. So, there is a significant effect of Natural Approach on speaking mastery at the X grade students of SMA Negeri 3 Padangsidimpuan. Keywords: Natural Approach and Students’ Speaking Mastery